Accelerated Pine (Pinus sylvestris) Rise in the Alpine Treeline Ecotone of the Swedish Scandes - Demographic Data 1973-2024 - Kullman, Leif; Öberg, Lisa (European Journal of Applied Sciences, 2025)
In a context of post-Little Ice Age (AD 1300-1900), climate warming and associated general progressive high-mountain landscape transformation, demographic changes in the pine (Pinus sylvestris) treeline ecotone were monitored over the years 1973-2024. The main focus was on a system of 18 permanent plots, randomly located within the pine treeline ecotone of the southern Swedish Scandes. Overall, unprecedented population growth (>300 %) was recorded, with a particularly high rate after the year of 2010, contingent on markedly increased seed viability, that significantly correlated with summer air temperature rise. The obtained changes are part of reponses to summer and winter regional climate warming and associated elevational treeline advance, encompassing the past 100 years or more. At a local scale, soil temperatures during the winter have increased over the past few decades, which has reduced the incidence of needle and shoot injuries and ensuing individual mortality, caused by winter desiccation and fine root dysfunction. Over the same period of time, winter precipitation (snow cover) has decreased. The latter circumstance implies earlier snow melt and a lowered risk of mechanical stress to young seedlings and saplings, as well as injuries by parasitic fungi. Another important aspect of decreased winter precipitation is that the growth period is prolonged, which may be a benefit to an evergreen species like Pinus sylvestris. The future evolution of the pine treeline ecotone is uncertain, given the unpredictable character of future climate change and its interactions with extant forest communities. Nevertheless, we may be currently witnesssing an embryonic new treeline ecotone under evolution, with pine as an increasingly important subalpine constituent.